Numerical Studies on the Impact of Traffic Loading on Embedded Pipes in Solar Energy Harvesting Concrete Pavement - Najeeb M.I.; Itam Z.; Alrubaye M.A.; Shaik Ahmad Fadzil S.M.M.; Zahari N.M.; Abu Bakar M.S.; Syamsir A.; Zawawi M.H.; Abdul Razak N. (MDPI, 2024)
Featured Application: Concrete Pavement Solar Collector Technology. The urban heat island (UHI) effect occurs when cities and towns warm up more than the surrounding rural areas because they have more structures and less vegetation and soil. The issue can be lessened by implementing a pavement solar collector (PSC) system, which converts heat from the pavements surface into thermal energy. In this work, the authors analyze the effect of pipe depth (85 mm to 50 mm) and spacing (200 mm to 100 mm) on the efficiency of heat extraction from the surface while taking pavement structural performance into account using the ANSYS Fluent program. The modeling approach was validated against the previous studies. According to the findings, a concrete water harvesting system may achieve the maximum outlet temperature with the least impact on traffic loading by using a distance of 100 mm and a depth of 85 mm. The loads impact is 51% less than that of the model that predicted the highest outlet temperature, and the outside temperature is reduced by 3.9%. The outcomes here demonstrated that concrete might be employed in the PSC system as an alternative to asphalt. 2023 by the authors.